2015
DOI: 10.1039/c5dt03814f
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a highly sensitive and selective “turn-on” fluorescent sensor for PO43− detection

Abstract: An efficient turn-on fluorescent sensor for PO4(3-) has been developed by rationally designing an in situ-generated iron(iii) complex with a 1,8-naphthalene-based Schiff base unit. The sensor exhibits high sensitivity and selectivity in both solution and solid-state film, even in the presence of other phosphate anions such as HPO4(2-) and H2PO4(-).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…−5 M的干扰离子(蓝条)和 1.0×10 −7 M三价铁离子(黑白条)后的荧光强度 [121] (网络版彩图) (1.50 mM)和EDTA (20 mM)的水:乙醇=1:1溶液中监测水凝胶膜的可逆性 [122] (网络版彩图) [37] (网络版彩图) 出对氟离子 [134] 、碘离子 [135] 和多卤离子 [136] [132] (网络版彩图) (c) 此化 学传感器在435 nm处的荧光强度比(I/I 0 , I 0 和I分别代表在溶液中无离子和含有阳离子时的荧光强度), 浓度为1 mM; mix是一种 混合溶液, 包含所有被测试的阳离子 [133] (网络版彩图) [137] (网络版彩图) , 对人类中性粒细胞弹性蛋白酶进行检测 的新型纤维素薄膜 [146] , 对多巴胺和单链脱氧核糖核酸 进行检测的石墨烯荧光薄膜也被陆续报道出来 [147] . [138] (网络版彩图) [143] (网络版彩图) 图 36 (a) JEVIPS的制备过程; (b) 荧光检测流程示意图; (c) 不同浓度的病毒溶液的荧光发射光谱(相同的色线代表有和没有 JEVIP存在的荧光曲线) [144] (网络版彩图)…”
Section: 其中就重金属离子而言 铅离子较为常见且毒性高 会unclassified
See 1 more Smart Citation
“…−5 M的干扰离子(蓝条)和 1.0×10 −7 M三价铁离子(黑白条)后的荧光强度 [121] (网络版彩图) (1.50 mM)和EDTA (20 mM)的水:乙醇=1:1溶液中监测水凝胶膜的可逆性 [122] (网络版彩图) [37] (网络版彩图) 出对氟离子 [134] 、碘离子 [135] 和多卤离子 [136] [132] (网络版彩图) (c) 此化 学传感器在435 nm处的荧光强度比(I/I 0 , I 0 和I分别代表在溶液中无离子和含有阳离子时的荧光强度), 浓度为1 mM; mix是一种 混合溶液, 包含所有被测试的阳离子 [133] (网络版彩图) [137] (网络版彩图) , 对人类中性粒细胞弹性蛋白酶进行检测 的新型纤维素薄膜 [146] , 对多巴胺和单链脱氧核糖核酸 进行检测的石墨烯荧光薄膜也被陆续报道出来 [147] . [138] (网络版彩图) [143] (网络版彩图) 图 36 (a) JEVIPS的制备过程; (b) 荧光检测流程示意图; (c) 不同浓度的病毒溶液的荧光发射光谱(相同的色线代表有和没有 JEVIP存在的荧光曲线) [144] (网络版彩图)…”
Section: 其中就重金属离子而言 铅离子较为常见且毒性高 会unclassified
“…a) Chemical structure of P and FeP. Fluorescence emission spectra (λ=531 nm) of FeP in THF-water mixtures upon the addition of various cations (b) and anions (c)[138] (color online).存在一些问题. 例如, (1) 荧光淬灭法仍然是荧光薄膜图 34 (a) 薄膜的化学结构及制作工艺; (b) 层间厚度对Ag/吖啶黄纳米复合膜中Acf荧光强度的影响; (c) Ag-PES、Ag-PES/ PEI/(PAA/CS) 3 和Ag-PES/(PAA/CS) 3 /P11(Acf)薄膜的紫外-可见吸收光谱; (d) ACF在不同基底上的荧光光谱; (e) 在不同碱基长 度的DNA存在下, Acf在Ag-PE/PEI/(PAA/CS) 3 /DNA(ACF)膜上的荧光光谱; (f) 11、20和35个碱基的DNA序列, ex=450 nm (a) Chemical structure and fabrication technology of thin films.…”
unclassified
“…For instance, acid rain is made from excessive emission of NO 3 – and SO 4 2– , which result from burning fossil fuels and automobile exhausts in the air. Not only are halogen ions extremely irritating and highly toxic to human bodies, but they are also very corrosive to many substances. , About PO 4 3– , as a derivative of phosphorus, plays a vital role in the process of living things such as gene regulation, genetic material, signal transmission, and energy storage. , From another perspective, PO 4 3– is a common pollutant anion of industrial production in aquatic ecosystems, which leads to overgrowth of algae and eutrophication of water. Besides, excessive phosphate and its derivatives can also affect the absorption of calcium ions in the human bodies and cause irreversible harm to people’s life. As a pollutant anion, PO 4 3– possesses less binding reactive sites and lower reactivity, so detection of PO 4 3– emerges a major challenge in the field of chemosensors. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a continuous need to develop novel, selective, sensitive, and inexpensive techniques in order to detect and discriminate from their respective habitats . The nanoparticle‐based sensory materials for Cu(II) and phosphate ion have been designed and synthesized by different research groups . It has been observed that the dipicolylamine group is considered as a potential chelator for some metal ions.…”
Section: Role Of Truxene System In Photocatalytic Processesmentioning
confidence: 99%